Peranan Guru Pendidikan Agama Islam Dalam Pembentukan Karakter Islami: (Studi Kasus Siswa MTs. al Huriyah Rejoso Pasuruan) - Mat Syaifi (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2022)
The focus of the research in this case is to find out the role of Islamic religious education teachers in forming the Islamic character of class VII MTs students. Al Huriyah Rejoso Pasuruan, knows about the formation of character education by Islamic religious education teachers for class VII MTs students. Al Huriyah Rejoso Pasuruan, knows the supporting and inhibiting factors for Islamic religious education teachers in forming the character of class VII MTs students. Al Huriyah Rejoso Pasuruan. This research was prepared based on field data using a qualitative approach. Data collected using participant observation, interviews and documentation. Meanwhile, for the analysis, the researcher used qualitative descriptive analysis techniques, namely in the form of a comprehensive description and description of the data collected about the actual situation. The results of this research indicate that Islamic religious education teachers play a role in shaping students' Islamic behavior. The role of teachers as educators in shaping students' Islamic behavior in class VII MTs students. Al Huriyah Rejoso Pasuruan is by always guiding and developing students to behave Islamically on a daily basis